KERAGAMAN JAMUR MAKROSKOPIS DI SEKITAR TITIK PEMASANGAN KAMERA TRAP DI KAWASAN HUTAN NAGARI PARIAN LUNANG, PESISIR SELATAN - Fichi Azra Syaqila; Dezi Handayani (Jurnal Biogenerasi, 2026)
Indonesia is a tropical country with a high level of biodiversity, including the diversity of macrofungi which play an important role as decomposers in the process of organic matter decomposition and in maintaining ecosystem balance. The Nagari Parian Lunang Forest Area, Pesisir Selatan, West Sumatra, has humid and relatively natural environmental conditions that potentially support the growth of various species of macrofungi. This study aims to identify the species of macrofungi, determine their potential uses, and analyze the influence of environmental factors on their distribution patterns. This research was a descriptive study conducted from September to December 2025 using an exploration method at several camera trap installation points. The mushrooms found were recorded based on their morphological characteristics, documented, and identified using the Collins Fungi Guide and related scientific literature. Environmental parameters measured included light intensity, soil temperature, and air humidity. The results showed that 28 species of macrofungi were successfully identified. Several species have potential uses as food sources, traditional medicine, and producers of bioactive compounds such as antibiotics and antitumor agents. The results of the Canonical Correspondence Analysis (CCA) indicated that light intensity, soil temperature, and air humidity influence the distribution patterns of mushrooms at each observation point.